Knowledge, attitude, and practice on food poisoning among pre-school food handlers in Kelantan, Malaysia - Hamzah, Nurul Ainun; Hadi, Nurul Hanani; Abdul Samad, Nurul Izzah; Anua, Siti Marwanis; Abdul Rahman, Haliza (Human Resource Management Academic Research Society, 2022)
A cross-sectional study was conducted to assess the Knowledge, Attitude, and Practice (KAP) on food poisoning among 191 food handlers in pre-schools in Kota Bharu, Kelantan, Malaysia using purposive sampling. The main instrument was a validated Malay self-administered questionnaire on food poisoning and data was analysed using univariate and multivariate analysis. The respondents had moderate knowledge (69.6 ±9.59), a positive attitude (86.2 ± 9.38), and good practice (84.9 ± 7.34). A slightly significant correlation was found between the score of knowledge and attitude (p=0.05, r=0.203). Age, educational level, and year of employment did not influence the KAP score on food poisoning (p>0.05). Even though training and education are essential in supplying the knowledge, however, it does not automatically translate to safe food handling practices. Therefore, continuous education and training should be organized to strengthen food handlers’ knowledge and attitude in areas that seem to be lacking.